2018
DOI: 10.1155/2018/7328465
|View full text |Cite
|
Sign up to set email alerts
|

International Scope of Emergency Ultrasound: Barriers in Applying Ultrasound to Guide Central Line Placement by Providers in Nairobi, Kenya

Abstract: Background While ultrasound (US) use for internal jugular central venous catheter (CVC) placement is standard of care in North America, most developing countries have not adopted this practice. Previous surveys of North American physicians have identified lack of training and equipment availability as the most important barriers to the use of US. Objective We sought to identify perceived barriers to the use of US to guide CVC insertion in a resource-constrained environment. Methods Prior to an US-guided CVC pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…Two other surveys showed that insufficient training and the limited availability of equipment are barriers to US use. 9 , 16 In accordance with previous surveys, our respondents identified the lack of formal training and unavailability of a US machine as barriers to USG-CVC placement.…”
Section: Discussionsupporting
confidence: 86%
“…Two other surveys showed that insufficient training and the limited availability of equipment are barriers to US use. 9 , 16 In accordance with previous surveys, our respondents identified the lack of formal training and unavailability of a US machine as barriers to USG-CVC placement.…”
Section: Discussionsupporting
confidence: 86%
“…In identifying perceived barriers to POCUS use, lack of equipment and education were the highest rated by a significant margin with 56% of respondents ranking them as “very important.” These results are similar to the findings of other surveys of US use in Vietnam and Kenya 11,12 . A survey performed in India of participants in a 4‐day US course in 2010 reported that 97% had “potential access” to an US machine in the near future, but this selection of participants at an emergency US course may not be representative of emergency physicians across India 13 .…”
Section: Discussionsupporting
confidence: 83%
“…These results are similar to the findings of other surveys of US use in Vietnam and Kenya. 11,12 A survey performed in India of participants in a 4-day US course in 2010 reported that 97% had "potential access" to an US machine in the near future, but this selection of participants at an emergency US course may not be representative of emergency physicians across India. 13 Lack of access to US equipment in India is problematic since in addition to the usual issues with acquiring hospital equipment (cost, institutional approval, etc.…”
Section: Discussionmentioning
confidence: 99%
“…POCUS is becoming standard of care for diagnostic and therapeutic interventions in a variety of clinical settings in highly developed medical systems (Bellamkonda et al 2015;Dietrich et al 2017;McLario and Sivitz 2015;Moore and Copel 2011). In recent years there has been an increasing effort to integrate POCUS into clinical care provided in resource-limited settings (Becker et al 2017;B elard et al 2018;Epstein et al 2018;Henwood et al 2017;Stanley et al 2017;Vinayak 2017;Vinayak and Brownie 2018;Zaver et al 2018). These efforts include initiatives to improve the relevance of ultrasound training programs enabling clinicians with a point-of care imaging modality.…”
Section: Introductionmentioning
confidence: 99%